1979
DOI: 10.1104/pp.63.2.354
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Synthesis of a Precursor to the Methionine-rich Polypeptide of the Zein Fraction of Corn

Abstract: The messenger ribonucleic acid fraction isolated from a protein bodyenriched fraction of developing corn (Zea mays L.) endosperm stimulated the incorporation of radioactive amino acids into at least five polypeptides when added to a wheat germ extract capable of protein synthesis. Of these, the two major polypeptides formed with messenger from freshly frozen corn were identified as precursors to zein A and B, the two major polypeptides of the prolamine fraction of corn meal (21,600 and 19,600 molecular weight)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
1986
1986

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In maize, the intracellular site of synthesis and cotranslational modifications of polypeptides corresponding to zeins-1 (19, 21.5, 22 kD Z1) have been extensively studied ( 3 -6, 14-16). However, the picture for the biosynthesis of low molecular weight zeins (10,14,15 kD Z2) is much less complete (22,30).…”
Section: Introductionmentioning
confidence: 99%
“…In maize, the intracellular site of synthesis and cotranslational modifications of polypeptides corresponding to zeins-1 (19, 21.5, 22 kD Z1) have been extensively studied ( 3 -6, 14-16). However, the picture for the biosynthesis of low molecular weight zeins (10,14,15 kD Z2) is much less complete (22,30).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on the synthesis of plant proteins has shown that the primary translation products of several classes of plant proteins are proteolytically cleaved during translation whereby a signal peptide is removed and the protein transported through the membrane of the endoplasmic reticulum. Among them are storage proteins as pea, soybean and broad bean vicilins [13,32,35], barley prolamins [7] and zein [5,16,19]. Other examples are enzymes such as c~-amylase in wheat [4], barley [23] and rice [20] and a protease inhibitor from tomato leaves [24].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for these differences are not understood at present. Evidence has been obtained for similar precursors in the storage proteins of barley and maize (6,8,18,24,36) and Burr et al (8) presented preliminary evidence that the additional sequence was located at the amino-terminus of a zein polypeptide. The storage proteins of French bean have also been shown to be synthesized in vitro as polypeptides of different size to those found in vivo (15), but it is not known whether these precursors are affected by membranes.…”
Section: Ep 4imentioning
confidence: 96%
“…The biosynthesis of storage proteins of legumes and cereals has been studied during seed maturation by in vivo pulse labeling (5,34) and by cell-free translation of polyribosomes and RNA (3,5,6,8,9,13,15,16,18,22,24,29,35,36). The synthesis and accumulation of individual storage proteins and their component polypeptides occur at well-defined stages during seed development (for review, see ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation